2018
DOI: 10.1186/s12862-018-1238-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution within a language: environmental differences contribute to divergence of dialect groups

Abstract: BackgroundThe processes leading to the diversity of over 7000 present-day languages have been the subject of scholarly interest for centuries. Several factors have been suggested to contribute to the spatial segregation of speaker populations and the subsequent linguistic divergence. However, their formal testing and the quantification of their relative roles is still missing. We focussed here on the early stages of the linguistic divergence process, that is, the divergence of dialects, with a special focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…We found no association between geographical isolation and within-community conflict in our sample ( χ 2 = 52.66, df = 44, p = 0.17; S2 Fig ). Therefore it is unlikely that geographical isolation promotes differentiation either by increasing social group cohesion [ 33 ] or intensifying within-group conflict over resources [ 58 ]. In summary, we argue that geographical isolation may have contributed to differentiation among Austronesian languages mostly by preventing the random loss of existing lexical items, despite also hindering the ability of novel lexical innovations to emerge and be utilised [ 38 , 59 ], rather than by affecting the internal social dynamics of isolated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no association between geographical isolation and within-community conflict in our sample ( χ 2 = 52.66, df = 44, p = 0.17; S2 Fig ). Therefore it is unlikely that geographical isolation promotes differentiation either by increasing social group cohesion [ 33 ] or intensifying within-group conflict over resources [ 58 ]. In summary, we argue that geographical isolation may have contributed to differentiation among Austronesian languages mostly by preventing the random loss of existing lexical items, despite also hindering the ability of novel lexical innovations to emerge and be utilised [ 38 , 59 ], rather than by affecting the internal social dynamics of isolated groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, population density, local interconnectedness and migrations were claimed to play a key role in cumulative cultural evolution by facilitating the emergence, diffusion and survival of linguistic innovations [18,21,[27][28][29][30]. In contrast, social, cultural and political settings [31,32] might also promote social group cohesion and the sharing of linguistic features within groups, which would reduce rates of linguistic differentiation [33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they fit especially well to linguistic typological data. Admixture models have been applied in linguistics to study language families (Reesink et al 2009) and dialects (Syrjänen et al 2016;Honkola et al 2018Honkola et al , 2019. The application of model-based clustering algorithms to linguistic data is discussed in depth elsewhere (Syrjänen et al 2016;Syrjänen 2021).…”
Section: Diachronic Patterns Of Typological Admixturementioning
confidence: 99%
“…Kipot ja Kielet research project (2018Kielet research project ( -2020 led by Päivi Onkamo and Outi Vesakoski; several Kone Foundation projects: UraLEX (2014UraLEX ( -2016 led by Unni-Päivä Leino;SumuraSyyni (2013SumuraSyyni ( -2016 and AikaSyyni (2017AikaSyyni ( -2021 led by Outi Vesakoski: OV, TH and YJ were funded by AikaSyyni. Research was also supported by the Turku University Foundation (Terhi Honkola) as well as Collegium for Transdisciplinary Studies in Archeology, Genetics and Linguistics, University of Tartu (2018-), and partly by the Estonian Research Council (grants No.…”
Section: Fundingmentioning
confidence: 99%
“…cross-cousin marriage practices may depend on a population's subsistence strategy) [ 26 ], the forms of words themselves have no fitness implications so linguistic differences are often used as neutral markers to track the diverging cultural histories of populations [ 27 ]. Using linguistic differences between municipalities in Finland, Honkola et al [ 28 ] found that diverging dialects were better predicted by ecological and cultural differences than geographical distance. This supports the view of cultural adaptation proponents who argue that cultural practices respond to challenges posed by particular environments [ 29 ].…”
Section: Introductionmentioning
confidence: 99%